Letter from Paul G. Kirk Jr. - Paul G. Kirk Jr.:::::: (1989)
This January 31, 1989 letter from Democratic National Committee Chairman Paul G. Kirk, Jr. encourages Democratic delegates to complete a University of Michigan survey studying the political activities of national convention delegates. The research, begun in 1972, aims to deepen understanding of the American party system and the role of party activists. Kirk urges delegates to participate so the study can provide comprehensive and accurate data for scholars and political leaders alike.